A Filled Function Approach for Nonsmooth Constrained Global Optimization. (2nd November 2010) - Wang, Weixiang; Shang, Youlin; Zhang, Ying
Abstract : A novel filled function is given in this paper to find a global minima for a nonsmooth constrained optimization problem. First, a modified concept of the filled function for nonsmooth constrained global optimization is introduced, and a filled function, which makes use of the idea of the filled function for unconstrained optimization and penalty function for constrained optimization, is proposed. Then, a solution algorithm based on the proposed filled function is developed. At last, some preliminary numerical results are reported. The results show that the proposed approach is promising.